Women’s Digital Solitude: Holofeminism and Female Privacy in the Age of Social Media - Akbaş, Arif (Fırat University, 2026)
This study examines women’s experiences of privacy in the digital age by theoretically discussing the concept of “Women’s Digital Solitude.” The primary aim of the research is to reveal how women’s digital representations on social media platforms are shaped along the axes of privacy, visibility, and solitude. Within this context, the newly developed theory of Holofeminism is employed to investigate the multi-layered modes of women’s existence in digital environments. Holofeminism (The Holistic Feminist Theory) is a novel feminist approach that goes beyond the notions of biological sex and gender; it incorporates multi-layered, multi-temporal, multi-spatial, and technological dimensions. The prefix “holo” derives from the Greek word holos (whole, entire) and represents a holistic, inclusive perspective. The study uses qualitative research methods, specifically critical discourse analysis and descriptive sociological approaches, to analyze women’s visual representations on social media content, particularly on Facebook, Instagram, and TikTok. The findings indicate that women are often compelled to display themselves on digital platforms; however, this visibility paradoxically generates feelings of solitude and loss of privacy. Holofeminism analyzes this contradiction within both technological and social contexts, defining digital solitude as a new form of privacy. This analysis suggests rethinking debates about women’s privacy within the frameworks of digital culture and artificial visuality, thereby contributing theoretically to the literature in women’s studies.

Bu çalışma, dijital çağda kadınların mahremiyet deneyimlerini inceleyerek “Kadınların Dijital Yalnızlığı” kavramını teorik bir çerçevede tartışmaktadır. Araştırmanın temel amacı, sosyal medya platformlarında kadınların dijital temsil biçimlerinin mahremiyet, görünürlük ve yalnızlık ekseninde nasıl şekillendiğini ortaya koymaktır. Bu bağlamda, yeni geliştirilen Holofeminizm kuramı aracılığıyla kadınların dijital ortamdaki çok katmanlı varoluş biçimleri incelenmiştir. Holofeminizm (Bütüncül Kadınlık Kuramı); kadın deneyimini sadece biyolojik cinsiyet ya da toplumsal cinsiyet kavramlarıyla sınırlamayan; bunun ötesine geçen, çok katmanlı, çok zamanlı, çok mekânlı ve teknolojik boyutları içeren yeni bir feminist yaklaşımdır. “Holo” ön eki, Yunanca holos (bütün, tüm) kökünden gelir ve bütünsel, kapsayıcı bir perspektifi temsil etmektedir. Çalışmada nitel araştırma yöntemlerinden eleştirel söylem analizi ve betimsel sosyolojik yaklaşım kullanılarak sosyal medya içerikleri (özellikle Facebook, Instagram ve TikTok) üzerinden kadınların görsel temsilleri analiz edilmiştir. Araştırma bulguları, kadınların dijital platformlarda sıklıkla kendilerini sergilemeye zorlandığını, ancak bu görünürlüğün paradoksal olarak bir yalnızlık ve mahremiyet kaybı hissi doğurduğunu göstermektedir. Holofeminizm, bu çelişkiyi hem teknolojik hem de toplumsal bağlamda analiz ederek dijital yalnızlığı yeni bir mahremiyet biçimi olarak tanımlar. Bu çözümleme kadın mahremiyetine dair tartışmaları dijital kültür ve yapay görsellik bağlamında yeniden düşünmeyi önererek, kadın çalışmaları literatürüne kuramsal bir katkı sunmaktadır.
Kadınların Dijital Yalnızlığı: Holofeminizm ve Sosyal Medya Çağında Kadın Mahremiyeti
Keywords: Women's Studies; Kadın Araştırmaları